Playing it safe but losing anyway – serotonergic signaling of aversive outcomes in dorsomedial prefrontal cortex in the context of risk-aversion - Macoveanu, Julian (Eur Neuropsychopharmacol, 2012)
Risk avoidance is an important determinant of human behavior. The neurotransmitter serotonin has long been implicated in processing aversive outcomes caused by risky decisions. However, it is unclear whether serotonin provides a neurobiological link between making a risk aversive decision and the response to an aversive outcome. Using pharmacological fMRI, we manipulated the availability of serotonin in healthy volunteers while performing a gambling task. The same group of participants was studied in three fMRI sessions: (i) during intravenous administration of the SSRI citalopram to increase the serotonergic tone, (ii) after acute tryptophan depletion (ATD) to reduce central serotonin levels, or (iii) without interventions. ATD and citalopran had opposite effects on outcome related activity in dorsomedial prefrontal cortex (dmPFC) and amygdala. Relative to the control condition, ATD increased and citalopram decreased the neural response to aversive outcomes in dmPFC. Conversely, ATD decreased and citalopram increased the neural response to aversive outcomes in left amygdala. Critically, these pharmacological effects were restricted to aversive outcomes that were caused by low-risk decision and led to a high missed reward. ATD and citalopram did not alter the neural response to positive outcomes in dmPFC, but relative to ATD, citalopram produced a bilateral increase in the amygdala response to large wins caused by high-risk choices. The results show a selective involvement of the serotonergic system in neocortical processing of aversive outcomes resulting from risk-averse decisions, thereby linking risk aversion and processing of aversive outcomes in goal-directed behaviors.